The Effect of Service and User Interface on Consumer Satisfaction in Remittances from South Korea to Indonesia through the GME Application - Anam, Khoerul; Wilis , Ratih Anggoro; Setyadi, Yusuf (West Science Business and Management, 2024)
This study aims to determine the Effect of Service and User Interface on Consumer Satisfaction of Remittances from South Korea to Indonesia through the GME Application. The method used in this study is quantitative with an explanatory research approach. From the SPSS output, it is known that the hypothesis criteria of the t test (partial) on the service variable are rejected when the sign > 0.05 and accepted when the sign > 0.05 SPSS test results show that 3,896 and H_o1 t_hitung≤t_tabel H_a1 t_hitung≥t_tabel,t_hitung t_tabel1,655 there is a linear relationship between the service and the user interface significantly  liniearity of 0.000 < 0.05. User interface variables are rejected when the sign > 0.05 and accepted when the sign > 0.05 SPSS test results show that 2,392 and H_o1 t_hitung≤t_tabel H_a1 t_hitung≥t_tabel,t_hitung t_tabel1,655 there is a linear relationship between the user interface to consumer satisfaction with significant  linearity of 0.018 < 0.05. It was concluded that the service and user interface affect customer satisfaction in sending money from South Korea to Indonesia through the application GME, is expected to provide more services in the process of transferring money between countries.